(untitled) (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2017)
This article makes a tour on the importance of religion to the communities originating in Chiapas, the dynamics sociocultural and religious in a community tseltal and as it pursues and linking the beliefs that at one time were based in the cosmovision and inheritances Maya tseltales. This research focuses on the community of Vicente Guerrero, Chiapas, located in the northern zone of Chiapas which is an area tseltal and where most of its inhabitants left the Catholic religion to assume various christian currents of type evangelical and pentecostal, fundamentally.